A preparation method of metallized ceramic silver paste
The nanosheet-shaped silver powder was prepared by the reverse microemulsion method and mixed with bismuth-based glass powder, which solved the problem of insufficient conductivity of silver powder in the existing conductive silver paste, and achieved higher conductivity and good binding strength.
Patent Information
- Application Number
- CN202411752142.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-12-02
AI Technical Summary
The conductive properties of silver powder in existing conductive silver pastes are insufficient, making it difficult to meet the broader application needs.
Nanoflake silver powder was prepared by reverse microemulsion method, and thoroughly mixed with bismuth-based glass powder and other oxides, and metallized ceramic silver paste was prepared by ball milling and defoaming.
More conductive channels are formed through line contact and surface contact, which improves the conductive properties of silver paste. After sintering, it has good bonding strength with the Al2O3 ceramic substrate and low volume resistivity.
Smart Images

Figure CN119207896B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ceramic metallization, in particular to a method for preparing a metallized ceramic silver paste. Background Art
[0002] Conductive paste, as a basic material in the field of electronic manufacturing, is an advanced electronic functional material that integrates multiple disciplines such as metallurgy, electronic technology, and chemical engineering. It is widely used due to its wide applicability, high quality, advanced technology, and high efficiency, and has become a key material for electrodes, interconnects, and component packaging. At present, the conductive phase in conductive silver paste is mainly silver powder. In order to improve the performance of conductive silver paste and meet broader application needs, the research on precious metal nano-crystallization in conductive paste has become a hot topic. Summary of the invention
[0003] Purpose of the invention: In view of the above technical problems, the present invention proposes a method for preparing metallized ceramic silver paste.
[0004] The technical solutions adopted are as follows:
[0005] A method for preparing a metallized ceramic silver paste is as follows:
[0006] Preparation of nano-flaky silver powder with a thickness of ≤1nm and an aspect ratio of ≥100;
[0007] Bi2O3, H3BO3, SiO2, TiO2, ZrO2, Ga2O3 and K2CO3 in a mass ratio of 50-60:10-15:4-6:1-3:1-3:2-4:2-4 are fully ground and heated to melt, first heated to 400-500°C and kept for 1-2h, then heated to 800-900°C and kept for 1-2h, then heated to 1200-1250°C and kept for 1-2h, the molten glass liquid is poured into water for water quenching, and the product after water quenching is ground and dried to obtain glass powder;
[0008] Mix glass powder, nano-flaky silver powder and organic carrier in a mass ratio of 1-5:60-80:30-40, and then degas after ball milling;
[0009] The preparation method of the nano-flaky silver powder is as follows:
[0010] Cyclohexane, isoamyl alcohol, surfactant and water are mixed to prepare W / O type microemulsion;
[0011] Add the silver ammonia solution to the microemulsion and mix well;
[0012] Then add the reducing agent and mix the reaction, let it stand, centrifuge, collect the precipitate, wash and dry;
[0013] The surfactant includes an ionic liquid and sodium dodecyl sulfate;
[0014] The mass ratio of the ionic liquid to sodium dodecyl sulfate is 1-5:1-5.
[0015] Furthermore, the ionic liquid is any one or more combinations of 1-tetradecyl-3-methylimidazolium acetate, 1-tetradecyl-3-methylimidazolium tetrafluoroborate, and 1-tetradecyl-3-methylimidazolium hexafluorophosphate.
[0016] Furthermore, the mass ratio of the cyclohexane, isoamyl alcohol, surfactant and water is 20-40:5-10:1-3:5-10.
[0017] Furthermore, the reducing agent is hydrazine hydrate and / or ascorbic acid.
[0018] Further, the organic carrier includes diethylene glycol butyl ether and ethyl cellulose;
[0019] The mass ratio of diethylene glycol butyl ether to ethyl cellulose is 4-6:1.
[0020] Beneficial effects of the present invention:
[0021] The invention provides a method for preparing a metallized ceramic silver paste. The silver powder in the conductive silver paste serves as a conductive phase and is the main source of the conductive ability of the silver paste. The principle of the silver powder forming a conductive path in the conductive paste is very complicated. So far, there is no conductive mechanism that can be applied to all conductive situations of the silver paste. The percolation theory mechanism believes that the direct contact between conductive fillers is a direct factor for forming a conductive path in the conductive silver paste. The invention adopts a reverse microemulsion method and uses ionic liquid and sodium dodecyl sulfate as surfactants. The prepared nano-flaky silver powder has a quasi-two-dimensional structure. The larger diameter-to-thickness ratio can form more conductive paths through line contact and surface contact. Under the same mass, the conductive performance of the silver paste prepared by the nano-flaky silver powder in the invention is better than that of the silver paste prepared by the spherical nano-silver powder.
[0022] Bismuth-based glass powder has similar properties to lead-based glass powder, and has advantages such as good chemical stability and low thermal expansion coefficient. Oxides such as Bi2O3, B2O3, and SiO2 can be well eutectic to form a glass network, making the glass forming temperature range wider. K2O can promote the transformation of [BO3] triangles into [BO4] tetrahedrons, making the molten glass powder network structure compact, thereby reducing the thermal expansion coefficient. Ga2O3 acts as a network modifier in the glass powder network structure and can be well eutectic with other oxides in the glass powder. The better the fluidity of the glass material, the better the flow and sinking of the glass after melting to form a better connection between the conductive layer and the ceramic substrate, and the better the formation of sintering necks between the nano-flake silver powders. The denser the structure of the conductive layer, the fewer holes, and the smaller the contact resistance between the particles, resulting in a decrease in the resistivity of the entire conductive layer and an improvement in the conductive performance.
[0023] The silver paste prepared by the invention has good bonding strength with the Al2O3 ceramic substrate after sintering, and has low volume resistivity and good electrical conductivity. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is the AFM image of the nano-flake silver powder prepared in Example 1;
[0025] Figure 2 is a height profile of the nano-flaky silver powder prepared in Example 1;
[0026] Figure 3 This is a surface SEM image of the conductive square after the metallized ceramic silver paste prepared in Example 1 was cured. DETAILED DESCRIPTION
[0027] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially. The techniques not mentioned in the present invention are all referenced to the prior art. Unless otherwise specified, the following examples and comparative examples are parallel experiments, using the same processing steps and parameters.
[0028] Embodiment 1:
[0029] This embodiment provides a method for preparing a metallized ceramic silver paste:
[0030] 60g of cyclohexane, 15g of isoamyl alcohol, 2g of 1-tetradecyl-3-methylimidazolium hexafluorophosphate, 2g of sodium dodecyl sulfate and 50ml of water were mixed to prepare a W / O type microemulsion, 3.4g of silver nitrate was dissolved in 15ml of water to obtain a silver nitrate solution, ammonia water was slowly added dropwise to the silver nitrate solution until the generated precipitate was completely dissolved to obtain a silver ammonia solution, the silver ammonia solution was added to the microemulsion and mixed, and then 0.5ml of 80% hydrazine hydrate was diluted with 10ml of water and added, and the mixture was stirred for reaction for 30min, and the mixture was allowed to stand for 10min and then centrifuged, the precipitate was collected, washed with water and ethanol and then dried to obtain a nano-flaky silver powder with a thickness of ≤1nm and an aspect ratio of ≥100. The thickness and width thereof were measured by AFM, and the results were as follows: Figure 1 and Figure 2 As shown, the longitudinal thickness of the nano-flake silver powder is about 0.81 nm, and the lateral width is about 750 nm;
[0031] Bi2O3, H3BO3, SiO2, TiO2, ZrO2, Ga2O3 and K2CO3 in a mass ratio of 55:15:6:2:1:2:2 are fully ground and heated to melt, first heated to 450°C at a rate of 5°C / min and kept warm for 1 hour, then heated to 850°C at a rate of 10°C / min and kept warm for 1 hour, then heated to 1250°C at a rate of 5°C / min and kept warm for 1 hour, the molten glass liquid is poured into water for water quenching, the product after water quenching is ground and dried to obtain glass powder;
[0032] Glass powder, nano-flaky silver powder, diethylene glycol butyl ether and ethyl cellulose in a mass ratio of 5:75:30:5 were mixed evenly and added into a ball mill, followed by ball milling for 1 hour in a planetary ball mill, and finally vacuum degassing for 10 minutes at a vacuum degree of 0.1 MPa.
[0033] Embodiment 2:
[0034] This embodiment provides a method for preparing a metallized ceramic silver paste:
[0035] 60g of cyclohexane, 15g of isoamyl alcohol, 2g of 1-tetradecyl-3-methylimidazolium tetrafluoroborate, 2g of sodium dodecyl sulfate and 50ml of water are mixed to prepare a W / O type microemulsion, 3.4g of silver nitrate is dissolved in 15ml of water to obtain a silver nitrate solution, ammonia water is slowly added dropwise to the silver nitrate solution until the generated precipitate is completely dissolved to obtain a silver ammonia solution, the silver ammonia solution is added to the microemulsion and mixed, 0.5ml of 80% hydrazine hydrate is diluted with 10ml of water and then added, and the mixture is stirred for reaction for 30min, the mixture is allowed to stand for 10min and then centrifuged, the precipitate is collected, washed with water and ethanol and then dried to obtain a nano-flaky silver powder with a thickness of ≤1nm and a diameter-to-thickness ratio of ≥100;
[0036] Bi2O3, H3BO3, SiO2, TiO2, ZrO2, Ga2O3 and K2CO3 in a mass ratio of 55:15:6:2:1:2:2 are fully ground and heated to melt, first heated to 450°C at a rate of 5°C / min and kept warm for 1 hour, then heated to 850°C at a rate of 10°C / min and kept warm for 1 hour, then heated to 1250°C at a rate of 5°C / min and kept warm for 1 hour, the molten glass liquid is poured into water for water quenching, the product after water quenching is ground and dried to obtain glass powder;
[0037] Glass powder, nano-flaky silver powder, diethylene glycol butyl ether and ethyl cellulose in a mass ratio of 5:75:30:5 were mixed evenly and added into a ball mill, followed by ball milling for 1 hour in a planetary ball mill, and finally vacuum degassing for 10 minutes at a vacuum degree of 0.1 MPa.
[0038] Embodiment 3:
[0039] This embodiment provides a method for preparing a metallized ceramic silver paste:
[0040] 60g of cyclohexane, 15g of isoamyl alcohol, 2g of 1-tetradecyl-3-methylimidazole acetate, 2g of sodium dodecyl sulfate and 50ml of water are mixed to prepare a W / O type microemulsion, 3.4g of silver nitrate is dissolved in 15ml of water to obtain a silver nitrate solution, ammonia water is slowly added dropwise to the silver nitrate solution until the generated precipitate is completely dissolved to obtain a silver ammonia solution, the silver ammonia solution is added to the microemulsion and mixed, 0.5ml of 80% hydrazine hydrate is diluted with 10ml of water and then added, and the mixture is stirred for reaction for 30min, the mixture is allowed to stand for 10min and then centrifuged, the precipitate is collected, washed with water and ethanol and then dried to obtain a nano-flaky silver powder with a thickness of ≤1nm and a diameter-to-thickness ratio of ≥100;
[0041] Bi2O3, H3BO3, SiO2, TiO2, ZrO2, Ga2O3 and K2CO3 in a mass ratio of 55:15:6:2:1:2:2 are fully ground and heated to melt, first heated to 450°C at a rate of 5°C / min and kept warm for 1 hour, then heated to 850°C at a rate of 10°C / min and kept warm for 1 hour, then heated to 1250°C at a rate of 5°C / min and kept warm for 1 hour, the molten glass liquid is poured into water for water quenching, the product after water quenching is ground and dried to obtain glass powder;
[0042] Glass powder, nano-flaky silver powder, diethylene glycol butyl ether and ethyl cellulose in a mass ratio of 5:75:30:5 were mixed evenly and added into a ball mill, followed by ball milling for 1 hour in a planetary ball mill, and finally vacuum degassing for 10 minutes at a vacuum degree of 0.1 MPa.
[0043] Comparative Example 1: is basically the same as Example 1, except that 1-tetradecyl-3-methylimidazolium tetrafluoroborate is replaced by an equal mass of sodium dodecyl sulfate, that is, 4 g of sodium dodecyl sulfate is added.
[0044] Comparative Example 2: The method is basically the same as Example 1, except that sodium dodecyl sulfate is replaced by an equal mass of 1-tetradecyl-3-methylimidazolium tetrafluoroborate, that is, 4 g of 1-tetradecyl-3-methylimidazolium tetrafluoroborate is added.
[0045] Comparative Example 3 is basically the same as Example 1, except that commercially available nano-grade silver powder (Pioneer Nano) is used instead of the homemade nano-flaky silver powder.
[0046] Comparative Example 4 is basically the same as Example 1, except that commercially available micron silver flakes (5-10 μm, Hongwu Materials Technology) are used instead of the homemade nano-flaky silver powder.
[0047] Comparative Example 5: is basically the same as Example 1, except that commercially available Bi2O3-B2O3-SiO2 glass powder (Suzhou Qiuyi New Materials) is used instead of the homemade glass powder.
[0048] Performance Test:
[0049] ① The hundred-grid test is used to measure the bonding strength of the silver paste after sintering on the Al2O3 ceramic substrate. The bonding strength is divided into 0-5 levels. The higher the level, the higher the bonding strength. The experimental steps are as follows:
[0050] 1. According to the provisions of ISO R1514 and ISO 2808, the silver pastes prepared in Examples 1-3 of the present invention and Comparative Examples 1-5 were respectively printed on an Al2O3 ceramic substrate by screen printing to form a 10 mm×10 mm×0.1 mm conductive layer and sintered at 900° C. to obtain the test pieces required for the test;
[0051] 2. Place the prepared test piece on a flat and sufficiently hard plate;
[0052] 3. Hold the handle of the grid cutter with your hand so that the multi-edged blade is perpendicular to the plane of the conductive layer;
[0053] 4. Hold the grid knife and apply force evenly, cut the conductive layer at a speed of 20-50 mm / s. Try to avoid shaking during the cutting process;
[0054] 5. Rotate the blade 90° and repeat the previous operation to cut the conductive layer twice to obtain a grid pattern.
[0055] 6. Use a soft brush to gently brush forward and backward along the diagonal line of the conductive layer 5 times each;
[0056] 7. Use 3M tape to stick on the grid area and press it smoothly with an eraser;
[0057] 8. Pull and remove the tape in a single smooth motion at an angle of 180°;
[0058] 9. Analyze the test results according to Table 1;
[0059] ;
[0060] ② Use a four-probe platform to measure the resistivity of the conductive layer. According to the provisions of ISO R1514 and ISO 2808, the silver pastes prepared in Examples 1-3 of the present invention and Comparative Examples 1-5 are respectively printed on an Al2O3 ceramic substrate by screen printing to form a 10 mm×10 mm×0.1 mm conductive layer and sintered at 900°C to obtain a conductive block required for the test. Then, the conductive block is placed in the center of the four-probe platform, and the four probes are allowed to fall naturally and vertically contact the conductive block to adjust the voltage and current, and multiple sets of data are recorded to obtain the average value;
[0061] The above test results are shown in Table 2 below:
[0062] ;
[0063] It can be seen from Table 2 above that the silver paste prepared in the present invention has good bonding strength with the Al2O3 ceramic substrate after sintering, and has low volume resistivity and good conductive performance.
[0064] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a metallized ceramic silver paste, characterized in that: The details are as follows: Preparation of nano-flaky silver powder with a thickness of ≤1nm and an aspect ratio of ≥100; Bi2O3, H3BO3, SiO2, TiO2, ZrO2, Ga2O3 and K2CO3 in a mass ratio of 50-60:10-15:4-6:1-3:1-3:2-4:2-4 are fully ground and heated to melt, first heated to 400-500°C and kept for 1-2h, then heated to 800-900°C and kept for 1-2h, then heated to 1200-1250°C and kept for 1-2h, the molten glass liquid is poured into water for water quenching, and the product after water quenching is ground and dried to obtain glass powder; The glass powder, nano-flaky silver powder and organic carrier are mixed and ball-milled in a mass ratio of 1-5:60-80:30-40, and then degassed; The preparation method of the nano-flaky silver powder is as follows: Cyclohexane, isoamyl alcohol, surfactant and water are mixed to prepare W / O type microemulsion; Add the silver ammonia solution to the microemulsion and mix well; Then add the reducing agent and mix the reaction, let it stand, centrifuge, collect the precipitate, wash and dry; The surfactant includes an ionic liquid and sodium dodecyl sulfate; The mass ratio of the ionic liquid to sodium dodecyl sulfate is 1-5:1-5.
2. The method for preparing the metallized ceramic silver paste according to claim 1, characterized in that: The ionic liquid is any one or more combinations of 1-tetradecyl-3-methylimidazolium acetate, 1-tetradecyl-3-methylimidazolium tetrafluoroborate, and 1-tetradecyl-3-methylimidazolium hexafluorophosphate.
3. The method for preparing the metallized ceramic silver paste according to claim 1, characterized in that: The mass ratio of the cyclohexane, isoamyl alcohol, surfactant and water is 20-40:5-10:1-3:5-10.
4. The method for preparing the metallized ceramic silver paste according to claim 1, characterized in that: The reducing agent is hydrazine hydrate and / or ascorbic acid.
5. The method for preparing the metallized ceramic silver paste according to claim 1, characterized in that: The organic carrier includes diethylene glycol butyl ether and ethyl cellulose; The mass ratio of diethylene glycol butyl ether to ethyl cellulose is 4-6:1.
Citation Information
Patent Citations
Method for preparing conductive silver paste from nano-silver modified flaky silver powder
CN118039248A
Optical glass, optical element and optical instrument
JP2018135252A